If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2a+6+5a-4=44
We simplify the equation to the form, which is simple to understand
2a+6+5a-4=44
We move all terms containing a to the left and all other terms to the right.
+2a+5a=+44-6+4
We simplify left and right side of the equation.
+7a=+42
We divide both sides of the equation by 7 to get a.
a=6
| 2a+6b-5a-b+1= | | 9x+13y=12000 | | x/6-5/8=7/8 | | -4(6s-2)=16 | | 8*4/7 | | 1.9(1/4)= | | 18n-5=6n+19 | | 3p-3=4p-7 | | 5/1/6(-2/5)= | | P=18+2x | | 234=-2/5x | | 4x-6-6x+4=0 | | 9x^(-1/2)=x^(1/6) | | 33=(2w-5)*w | | 33=w*(2w-5) | | 7a+5=5 | | 10-(w+3)-4w+5=w-12 | | 5[x+4]=35 | | cos(6x)+4cos(2x)=0 | | 35=w*(2w-5) | | 4x^3+2x=1 | | -7x-6y=-22 | | X^2/2=110 | | A=(28)(15) | | 14g+10.5g-19.58=-3(-15.3g-18.44) | | 8-3n=-19 | | 17/15 | | (5x^4)(3x^2)= | | 56/10 | | 6k=k^3+k^2 | | -9x+6=42 | | 14g+19.5g-10.58=-3(-15.3g-18.44) |